Potential Enhancement of the In-Situ Bioremediation of Contaminated Sites through the Isolation and Screening of Bacterial Strains in Natural Hydrocarbon Springs - Pietro Rizzo (Water, 2020)
Petroleum hydrocarbon contamination (PHC) is an issue of major concern worldwide. These compounds represent the most common environmental pollutants and their cleaning up is mandatory. The main goal of this research was to analyze microbial communities in a site in southern Italy characterized by the presence of hydrocarbons of natural origin by using a multidisciplinary approach based on microbiological, geological and hydrological investigations. Bacterial communities of two springs, the surrounding soils, and groundwater were studied through a combination of molecular and culture-dependent methodologies to explore the biodiversity at the study site, to isolate microorganisms with degradative abilities, and to assess their potential to develop effective strategies to restore the environmental quality. Next-generation sequencing revealed the dominance of species of the Proteobacteria phylum but also the presence of other autochthonous hydrocarbon-oxidizing microorganisms affiliated to other phyla (e.g., species of the genera Flavobacterium and Gordonia). The traditional cultivation-based approach led to the isolation and identification of 11 aerobic hydrocarbon-oxidizing proteobacteria, some of which were able to grow with phenanthrene as the sole carbon source. Seven out of the 11 isolated bacterial strains produced emulsion with diesel fuel (most of them showing emulsifying capacity values greater than 50%) with a high stability after 24 h and, in some cases, after 48 h. These results pave the way for further investigations finalized at (1) exploiting both the degradation ability of the bacterial isolates and/or microbial consortia to remediate hydrocarbon-contaminated sites and (2) the capability to produce molecules with a promoting effect for oil polluted matrices restoration.